Evaluation of two genera of benthic foraminifera for down-core paleotemperature studies in the western south atlantic (Brazilian Journal of Oceanography, 2006)
In this study we have compared the oxygen isotopic composition of two genera of benthic foraminifera (Uvigerina and Cibicidoides) from core-top samples with modern oxygen isotopic composition of seawater (delta18O). Based on a new relationship between delta18O and salinity for the mid-latitude western South Atlantic, we estimated the isotopic composition of equilibrium calcite (delta18Oeq) using two different equations: (1) O'Neil et al. (1969), modified by McCorkle et al. (1997) and (2) Kim & O'Neil (1997). When using (1), the small difference between delta18Oeq and delta18O of Uvigerina suggests that this genus precipitates its shell close to equilibrium with ambient seawater. The delta18O Cibicidoides data are 0.82 lower than the predicted (equilibrium) oxygen isotopic composition. Conversely, using (2) the Cibicidoides delta18O data show excellent agreement with the oxygen isotopic composition predicted from delta18O and water temperature while Uvigerina delta18O data are 0.69 higher than predicted oxygen isotope equilibrium values. Based on the evidences presented here and on the results from previous studies we suggest using the genus Cibicidoides and applying Kim & O'Neil's (1997) equation for down-core paleotemperature investigations. In the absence of enough Cibicidoides specimens we suggest using Uvigerina delta18O data and applying a correction factor of -0.69 .